Spot Urine Protein Excretion in the First Year Following Kidney Transplantation Associates With Allograft Rejection Phenotype at 1-Year Surveillance Biopsies: An Observational National-Cohort Study - Oblak, Manca; Mlinšek, Gregor; Kojc, Nika; Frelih, Maja; Buturović-Ponikvar, Jadranka; Arnol, Miha (Frontiers in Medicine, 2021)
Introduction. Urine protein excretion is routinely measured to assess kidney allograft injury, but the diagnostic value of this measurement for kidney transplant pathology remains unclear. Here we investigated whether spot urine protein excretion in the first year following transplantation associates with allograft rejection phenotype at 1-year surveillance biopsies and de-novo occurrence of donor-specific antibodies (DSA). Patients and Methods. This prospective, observational national-cohort study included 139 non-sensitized patients who received a deceased donor kidney transplant between Dec 2014 and Dec 2018. All patients received basiliximab induction and tacrolimus-based immunosuppression. Estimated protein excretion rate (ePER) was calculated monthly from spot urine protein-to-creatinine ratios. At 1 year, all recipients underwent surveillance graft biopsy and were screened for de-novo DSA. Screening-positive sera were subjected to single antigen bead (SAB) testing. The occurrence of de-novo DSA was determined based on SAB reactivity patterns using a mean fluorescence intensity threshold >1000. Results. Among the 139 study patients, 27 patients (19%) had histologic evidence of T cell-mediated rejection (TCMR), and 9 patients (7%) had histologic evidence of antibody-mediated rejection (AMR) at 1-year surveillance biopsy. One year after transplant, 19 patients (14%) developed de-novo DSA. Compared with patients without rejection and no de-novo DSA, mixed-effects linear regression analysis showed a significant difference in slope of ePER during the first year in patients with AMR and de-novo DSA at 1 year (46, 95% CI 25 to 68 mg/day/1.73 m2 per month and 34, 95%CI 20 to 49 mg/day/1.73 m2 per month, respectively). Patients with vascular TCMR also showed a significant difference in ePER slope over time compared with patients with nonrejection findings (31, 95% CI 9 to 52 mg/day/1.73 m2 per month). The discriminatory power of ePER for intragraft rejection processes was better in patients with AMR (AUC 0.95, 95%CI 0.90–0.99; P<0.001) than in those with TCMR (AUC 0.68, 95%CI 0.59–0.79; P=0.002), with 89% sensitivity and 93% specificity for proteinuria >550 mg/day/1.73m2. Conclusions. An increase in ePER in the first year following kidney transplantation associates with AMR, vascular TCMR and de-novo DSA at 1 year and may be used as a non-invasive clinical marker of intragraft endothelial cell injury.